Moisture Content and Aromatic Compounds Determination in Transformer Oil Using Spectral Method - Kozlov V.K.; Kurakina O.E. (Problems of the Regional Energetics)
During operation, resulting from the thermochemical and electrical effects, the performance of the transformer oil decreases due to the measurement of the structural group composition. An increase in the content of the aromatic hydrocarbons leads to the appearance of a precipitate, and as well as due to its hygroscopicity, an increase in the moisture content. The latter is one of the transformer oil parameters that determines its quality. In power equipment, the presence of moisture of the order of 10 grams of water per ton of oil is allowed. At elevated water concen-trations, there is a risk of the power transformers’ failure. The aim of the work was to develop new methods for determining the aromatic compounds and water contents in the transformer oil in small quantities. This goal was achieved by conducting spectral studies of the transformer oil samples in the UV range and constructing correlation lines to determine the moisture content and concentration of aromatic compounds. The most significant result of the article was the estab-lishment of correlations between the optical density of the transformer oil in the region of 530 nm and the concentration of aromatic compounds and between the optical density in the region of 980 nm and moisture content in the oil. The significance of the obtained results lies in the fact that the optical method for determining the moisture content and aromatic hydrocarbons in transformer oils, using the constructed correlation lines, is highly accurate and does not require the use of additional reagents and complex calculations.